C/EBPβ and YY1 bind and interact with Smad3 to modulate lipopolysaccharide‐induced amelotin gene transcription in mouse gingival epithelial cells. Issue 2 (27th December 2018) - Nakayama, Yohei; Kobayashi, Ryoki; Iwai, Yasunobu; Noda, Keisuke; Yamazaki, Mizuho; Kurita‐Ochiai, Tomoko; Yoshimura, Atsutoshi; Ganss, Bernhard; Ogata, Yorimasa
Abstract : Junctional epithelium (JE) develops from reduced enamel epithelium during tooth formation and is critical for the maintenance of healthy periodontal tissue through ensuring appropriate immune responses and the rapid turnover of gingival epithelial cells. We have previously shown a relationship between inflammatory cytokines and expression of JE‐specific genes, such as amelotin (AMTN), in gingival epithelial cells. Here, we elucidated the effects of Porphyromonas gingivalis ‐derived lipopolysaccharide ( Pg LPS) on Amtn gene transcription and the interaction of transcription factors. To determine the molecular basis of transcriptional regulation of the Amtn gene by Pg LPS, we performed real‐time PCR and carried out luciferase assays using a mouse Amtn gene promoter linked to a luciferase reporter gene in mouse gingival epithelial GE1 cells. Gel mobility shift and chromatin immunoprecipitation assays were performed to identify response elements bound to LPS‐induced transcription factors. Next, we analyzed protein levels of the LPS‐induced transcription factors and the interaction of transcription factors by western blotting and immunoprecipitation. LPS increased Amtn mRNA levels and elevated luciferase activities of constructs containing regions between −116 and −238 of the mouse Amtn gene promoter. CCAAT /enhancer‐binding protein ( C/EBP ) 1–, C/EBP2 – and Ying Yang 1 ( YY1 )–nuclear protein complexes were increased by LPS treatment. Furthermore, we identified LPS‐modulated interactions with C/EBPβ, YY1 and Smad3. These results demonstrate that Pg LPS regulates Amtn gene transcription via binding of C/EBPβ–Smad3 and YY1–Smad3 complexes to C/EBP1, C/EBP2 and YY1 response elements in the mouse Amtn gene promoter. Abstract : Porphyromonas gingivalis lipopolysaccharide (LPS)‐induced physical interactions between CCAAT /enhancer‐binding protein β (C/EBPβ), Ying Yang 1 (YY1) and Smad3 upregulate amelotin ( Amtn ) gene transcription via mitogen‐activated protein kinase kinase 1/2 (MEK1/2), phosphatidylinositol 3‐kinase (PI3‐K) and Smad2/3 pathways in gingival epithelial cells. These findings raise the possibility of an association between induced C/EBPβ and YY1 in inflammation and a constitutive interaction with Smad3 in gingival epithelial cells.